Strain-induced martensite reversion in 18Cr–8Ni steel – transmission Kikuchi diffraction study. Issue 5 (24th March 2018) - Cios, G.; Tokarski, T.; Bała, P.
ABSTRACT: Reverse transformation of strain-induced martensite (SIM) was studied in the 18Cr–8Ni stainless steel. Microstructure analysis was performed on samples in an as-deformed state and after reversion annealing at 873 and 973 K, using the transmission Kikuchi diffraction. The primary, as well as reversed, austenite possesses the Kurdjumov–Sachs crystallographic orientation relationship, with respect to the SIM. The reverted austenite keeps one orientation within all reverted grains, regardless of the applied heating procedure, where the amount of reverted austenite depends only on the annealing temperature.